Meta-Analysis: The Effect of Using a Virtual Laboratory to Improve Students' Understanding of Physics Concepts - Rahmi, Annisa; Hidayati, Hidayati (Journal of Innovative Physics Teaching, 2023)
This study aims to: (1) analyze the model/strategy/method of using virtual laboratories in learning physics, (2) analyze the effect of virtual laboratories in learning physics on increasing students' understanding of concepts. The method used in this research is meta-analysis. The collected articles totaled 20 articles published in the last 10 years in national and international journals. Data analysis was performed using predetermined instruments and effect size formulas. The results of the research are learning models/learning strategies/learning methods for using virtual laboratories in physics learning to improve students' understanding of concepts, there are 6 learning models, and 2 learning approaches. The inquiry learning model is the most widely used. static fluid material has a good effect on students' understanding of concepts. with an average effect size value of 1.81 with a high influence category.